Digital processors and their role in the perception of the photographic image (Movie poster as a model) (Journal of the College of Basic Education, 2022)
The cinematic poster is one of the most important means that aims to communicate the idea of ​​a specific topic or movie. The designers of the advertising poster seek to use different types of treatments by reaching the largest possible number of people coming to the movie shows. Hence the current study, which includes the first chapter, the problem, the goal, the importance, and the definition of terms, the second chapter, which includes the first topic, in which the movie poster is presented (the messages of the poster and the role of technology in the development of the art of the poster), and the second topic includes (digital processing of the photographic image and its requirements and Raster method, vector method, and software types for digital image processing